Understanding community-based participatory research through a social movement framework: a case study of the Kahnawake Schools Diabetes Prevention Project - Marie-Claude Tremblay (BMC Public Health, 2018)
Abstract Background A longstanding challenge of community-based participatory research (CBPR) has been to anchor evaluation and practice in a relevant theoretical framework of community change, which articulates specific and concrete evaluative benchmarks. Social movement theories provide a broad range of theoretical tools to understand and facilitate social change processes, such as those involved in CBPR. Social movement theories have the potential to provide a coherent representation of how mobilization and collective action is gradually developed and leads to systemic change in the context of CBPR. The current study builds on a social movement perspective to assess the processes and intermediate outcomes of a longstanding health promotion CBPR project with an Indigenous community, the Kahnawake Schools Diabetes Prevention Project (KDSPP). Methods This research uses a case study design layered on a movement-building evaluation framework, which allows progress to be tracked over time. Data collection strategies included document (scientific and organizational) review (n = 51) and talking circles with four important community stakeholder groups (n = 24). Results Findings provide an innovative and chronological perspective of the evolution of KSDPP as seen through a social movement lens, and identify intermediate outcomes associated with different dimensions of movement building achieved by the project over time (mobilization, leadership, vision and frames, alliance and partnerships, as well as advocacy and action strategies). It also points to areas of improvement for KSDPP in building its potential for action. Conclusion While this study’s results are directly relevant and applicable to the local context of KSDPP, they also highlight useful lessons and conclusions for the planning and evaluation of other long-standing and sustainable CBPR initiatives. The conceptual framework provides meaningful benchmarks to track evidence of progress in the context of CBPR. Findings from the study offer new ways of thinking about the evaluation of CBPR projects and their progress by drawing on frameworks that guide other forms of collective action.